2017
DOI: 10.1007/s40279-017-0678-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants and Anterior Cruciate Ligament Rupture: A Systematic Review

Abstract: BackgroundStudies have shown a familial predisposition for anterior cruciate ligament (ACL) rupture and have been followed by genetic-association studies on polymorphisms in candidate genes in recent years. To date, no systematic review with a best-evidence synthesis has evaluated the influence of genetics on this devastating knee injury.ObjectiveOur objective was to evaluate the association between genetic variants and ACL rupture.MethodsWe performed an extensive search in Embase, MEDLINE, Web of Science, Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 65 publications
0
73
0
Order By: Relevance
“…Polymorphisms in FBN2, VEGFA, KDR, COL1A1, DCN, ACN (also known as ACIN1), BGN, LUM and COL5A1 (many of which encode ECM proteins and growth factors) and interactions between COL5A1 and COL12A1 gene variants 94 are linked to human ACL rupture [95][96][97][98][99] . Genetic associations with human ACL rupture found a COL1A1 SNP that was replicated in several studies 98,[100][101][102][103][104] .…”
Section: Knee Cruciate Ligament Rupturementioning
confidence: 76%
“…Polymorphisms in FBN2, VEGFA, KDR, COL1A1, DCN, ACN (also known as ACIN1), BGN, LUM and COL5A1 (many of which encode ECM proteins and growth factors) and interactions between COL5A1 and COL12A1 gene variants 94 are linked to human ACL rupture [95][96][97][98][99] . Genetic associations with human ACL rupture found a COL1A1 SNP that was replicated in several studies 98,[100][101][102][103][104] .…”
Section: Knee Cruciate Ligament Rupturementioning
confidence: 76%
“…This fluorescence makes it possible to discriminate between the three types of populations we have discussed previously (Figure 2) [5]. Recent studies have shown the importance of the individual genetic component, considered as an IF, in the non-contact injuries produced in the soft tissues [6][7][8][9]. All these studies indicate that there is a strong (more than 50%) genetic influence on the nature if injuries occurring.…”
Section: Genetic Variation and Detection Methodsmentioning
confidence: 85%
“…Over the last decade, 33 different single nucleotide polymorphisms (SNPs) of various genes have been investigated for association with ACL tear 5-7. COL1A1 rs1800012 polymorphism was the first specific gene polymorphism to be positively associated with ACL tear 3,4 . It is also the most extensively investigated SNP in the literature with various research teams having investigated the association between COL1A1 SNPs and ACL tear in different Caucasian population subsets with mixed results [5][6][7][8] . However, till date, there is no data from the Asian continent on the association of COL1A1 SNPs and ACL tear 7 .…”
Section: Introductionmentioning
confidence: 99%